'Mum's the Word': Predictors and Outcomes of Weight Concerns in Pre-Adolescent and Early Adolescent Girls - Thogersen-Ntoumani, Cecilie; Ntoumanis, Nikos; Chatzisarantis, Nikos; Vlachopoulos, S.; Katartzi, E.; Nikitaras, N. (2016)
Predictors and outcomes of weight concerns in pre-adolescent and adolescent girls are well known, but few models have incorporated concerns reported directly by mothers as a predictor, and both eating and exercise outcomes. Using questionnaires, a comprehensive model of 232 pre-adolescent and early adolescent girls’ weight concerns, eating restraint, and exercise behavior was tested. Structural equation modeling showed that daughters’ weight concerns were predicted primarily by their perceptions of their mothers’ concerns about the daughters’ weight, as well as by daughters’ BMI, appearance conversations with friends, and perceived media pressure. Mothers’ concerns with their daughters’ weight were indirectly associated with daughters’ own concerns, via the daughters’ perceptions of their mothers’ concerns. Daughters’ concerns with their weight were a strong predictor of eating restraint, but not exercise behavior.